The Concept Of Physical Education and Its Integration With Mental Health According to The Qur'An and Hadith - Eliwatis, Eliwatis; Rusydi, Rusydi; Charles, Charles; Maimori, Romi; Herawati, Susi (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Physical education in the view of Islam cannot be underestimated, because between the physical and the spiritual man is a unity. When physical education is carried out, it actually includes education for the human spirit, and vice versa. A popular motto is "al-'aqlu al-saliim fii al-jismi al-saliim", that has meaning a healthy soul there is a strong body. But in fact, physical education is often neglected because it focuses more on education that fills and develops spiritual potential. It will make human development completely unattainable. This paper tries to explain what and how the concept of physical education material contained in the Qur'an and Hadith, as well as its relationship to human health physically and psychologically. The research method used is descriptive qualitative through library research, therefore the source of data in this study is literature related to the discussion, with the data collection method is literature study (book survey). Data analysis using content analysis method which is descriptive analysis. The results showed that physical education is closely related to human health both physically and psychologically, including worship activities such as prayer and fasting, sports activities such as archery, horse riding and swimming and also activities related to hygiene and diet. This study concludes that the physical education material contained in the Qur'an and Hadith does not only focus on human physical health and development, but actually contains aspects of education and guidance on human mental/spiritual health.